Genetic basis of atherosclerosis, ischemic stroke and lipoprotein oxidation : with special reference to HDAC9 and MMP12 genes - Mäkelä, Kari-Matti (Acta Universitatis Tamperensis, 2015)
Tiivistelmä.
Keywords: Ischemic Attack, Transient : genetics; Lipoproteins, LDL; Atherosclerosis : genetics; ateroskleroosi; iskemia; riskitekijät; perimä; geenit; lipoproteiinit; hapettuminen